2002
DOI: 10.1046/j.1365-2648.2002.02428.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the pain and symptom assessment record (PSAR)

Abstract: There were many challenges in this project and lessons learned will be discussed. Based on the results, the tool has been modified and is currently utilized in diverse settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 27 publications
1
28
0
1
Order By: Relevance
“…21 Titler et al 22 found that increasing decision aids in practice improves clinician decision making and results in better pain management for patients. Some examples of pain decision-making aids include pain severity scales on patient observation charts, [23][24][25] wall posters reminding patients to tell staff about their pain and to remind staff to ask about patient's pain; pocket-sized equi-analgesic charts and pain protocols; and localized evidence based practice guidelines. 26 When considering improving pain management for patients multiple strategies have been shown to be a greater benefit in fostering evidence based practice.…”
Section: Discussionmentioning
confidence: 99%
“…21 Titler et al 22 found that increasing decision aids in practice improves clinician decision making and results in better pain management for patients. Some examples of pain decision-making aids include pain severity scales on patient observation charts, [23][24][25] wall posters reminding patients to tell staff about their pain and to remind staff to ask about patient's pain; pocket-sized equi-analgesic charts and pain protocols; and localized evidence based practice guidelines. 26 When considering improving pain management for patients multiple strategies have been shown to be a greater benefit in fostering evidence based practice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have shown that nurses have a positive perception of Screening for Distress tools, considering them as reasonably quick to complete [5,27]. However, some reported that nurses may also be concerned by the burden that Screening for Distress tools may add in terms of workload and time consumption [18], as well as by the lack of knowledge and training they received on Screening for Distress [3,21,24].…”
Section: Facilitators and Barriersmentioning
confidence: 99%
“…However, some reported that nurses may also be concerned by the burden that Screening for Distress tools may add in terms of workload and time consumption [18], as well as by the lack of knowledge and training they received on Screening for Distress [3,21,24]. Other barriers reported in the literature include the lack of an intimate space to perform Screening for Distress with the patient [3], cancer patients' difficulties in understanding or completing the Screening for Distress questionnaire [5,31], as well as poor interest or collaboration from other oncology team members and other organizational barriers [21].…”
Section: Facilitators and Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…69 A similar endeavor has been reported to develop a common symptom assessment and management tool across agencies working in palliative care in Ottawa. 71 Finally, outcome elements consistent with the consumer perspectives of quality health care (staying healthy, getting better, living with illness/disability, and coping with end of life) were incorporated into the structure of a national healthcare quality report, although there is no evidence that these positive outcomes are in any existing databases or that the 1996 conference and publications had any direct effect on this report. 4 With respect to research capitalizing on natural experiments, Aiken has been testing relationships among structural, process, and mortality/morbidity outcomes using a combination of administrative databases and primary data collection since the early 1990s.…”
Section: Capitalizing On Natural Experiments and Datasetsmentioning
confidence: 99%